Theologi Kebatinan Nu‘Mān Ibn Ḥayyūn Dalam Penafsiran Safīnah Dan Fulk Pada Kitab Asās Al-Ta’wīl - Husen, Mohammad; Luthfillah, Dluha (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2021)
This article focuses on the meaning of Nu'mān ibn Ḥayyūn for the words al-safinah and al-fulk in the Asās al-Ta'wil book. It also explains, using Gadamer's hermeneutical theory, the way Nu'man's interpretation on safīnah and fulk appears and how its historical relevance in Nu'mān's life. Nu'mān is a ta'wīl expert from the Syī'ah Ismā'īliyyah group who has produced many scientific works. The Asās al-Ta'wīl, contains Nu'man's interpretation of the stories of the prophets, which are the philosophical, spiritual and 'essence' of the al-Qur'an. The academic problem of this research originated from Nu'mān's representation of the word safīnah in Q.S. 29:15 concerning the ark of the Prophet Nūḥ. He interprets Safinah as proselityzing science / truth. Da'wah al-ḥaq is like a boat swinging over the ocean of knowledge. In his interpretation, there is a bias of Shī'ah ideology which is only carried out by Nu'mān, not other Shi'ite scholars. This study uses a hermeneutical approach with Gadamer's theory. This theory is used to explore the internal and extrenal aspects of the text that influence the results of Nu'mān Ibn Ḥayyūn's representations.